HERMENEUTIKA SEBAGAI METODE TAFSIR AL-QUR'AN DAN KONTROVERSI PENGGUNAANNYA - Akhmad Roja Badrus Zaman (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2017)
Nowadays, the study of philosophy has been much distribute of thoughts. Well that idea was in the sector of the humanities and Islamic studies. In Islam, has a lot use of methodology of philosophy developed by western civilization. Methods suchs as realism, empiricism and phenomenology have been become the paradigm to get the truth. And also latest method that used that is a method of a hermeneutic. A methods of interpretation in epistemology that will bring a new way to understand science of Islam, like Tafseer of The Qur’an. There is controversy inusing hermeneutical approaches for understanding the holy Qur’an. One group rejects it, while the others accepts it. This study will explore both arguments and will argue that in fact the two groups of tenets can be communicated and can be combined into one single purpose, that is applying the Qur’anic teachings in the islamic societies, eventhough through different methodstat sometimes each of them has distinct conclusion. The sigificance of this study is to show that the hermeneutic is an alternative to develop Qur’anic exegesis method.